Seasonal Assessment of Heavy Metal Pollution in Tropical Mangrove Sediments (Goa, India) - Savita Kerkar*, Kuldeep Attri and (Journal of Ecobiotechnology, 2011)
Mangrove swamps along the Mandovi estuary, Goa are exposed to an influx of metal effluents from the ferromanganese mining activities. The present study was carried out to assess the seasonal concentrations of metals in the sediments of Divar, an anthropogenically-influenced mangrove swamp in the Mandovi estuary, and compared to Tuvem along the Chapora River, a relatively pristine mangrove site. In both the sites, the average heavy metal concentration in sediments decreased in the order: Fe > Mn > Zn > Cu > Co > Pb > Cr and showed a marked seasonal variability (p< 0.001; df=2). However, the Pollution Load Index (PLI) for Divar sediments was far greater (1.65-2.19) than that of Tuvem (0.91-1.3) reflecting the intensity of anthropogenic inputs into the ecosystem. Further, Muller geochemical index values for Divar sediments indicated that during pre and post-monsoon season, the sediments were moderately contaminated with Fe whereas at Tuvem, the sediments were below contamination levels. The comparison with Screening Quick Reference Table (SQuiRT) also revealed the poor sediment quality for Divar. The transport of ferromanganese ore along the Mandovi River could be a major source of the entry of heavy metals in this riverine system. The Effect Range- Low (ER-L) values for these elements exceeded the reference values suggesting a potential eco-toxicological risk to the benthic organisms and a possible transfer to higher trophic levels.